High‐resolution polarimetric X‐band weather radar observations at the Cabauw Experimental Site for Atmospheric Research. (1st November 2013) - Otto, Tobias; Russchenberg, Herman W. J.
<x xml:space="preserve">Abstract</x> In 2007, the horizontally scanning polarimetric X‐band radar IDRA (IRCTR Drizzle Radar) was installed on top of the 213 m high mast at the Dutch meteorological observatory Cabauw Experimental Site for Atmospheric Research (CESAR) at Netherlands. This radar complements a large variety of measurement instruments at CESAR by providing information on the horizontally spatial distribution and the temporal evolution of precipitation around the site. IDRA is a frequency‐modulated continuous‐wave radar developed at TU Delft's International Research Centre for Telecommunications and Radar (IRCTR). IDRA is designed to provide a high spatial resolution (down to 3 m in range) at a temporal resolution of 1 min. Its central frequency of 9.475 GHz, sensitive receivers with a large dynamic range, and the possibility to adjust the power of the transmitted signal permit IDRA to measure the whole spectrum of meteorological echoes from low‐level clouds and drizzle to heavy convective rain. Similarly to most data collected at CESAR, also the data collected by IDRA are freely available for scientific purposes. IDRA data are stored at the Dutch 3TU.Datacentrum in order to make it easily accessible for everyone. In this article, we outline the IDRA dataset, including details on the data acquisition, processing, and possible applications.